Phenotypic plasticity of early myogenesis and satellite cell numbers in Atlantic salmon spawning in uplant and lowland tributaries of a river system - Johnston, Ian Alistair; McLay, HA; Abercromby, M; Robins, D (2000)
Early myogenesis was studied in the offspring of Atlantic salmon (Salmo salar L.) spawning in a lowland (Sheeoch) and an upland (Baddoch) tributary of the River Dee System, Aberdeenshire, Scotland. Eggs from each population were incubated at the simulated natural thermal regimes of each stream, which was on average 2.8 degrees C cooler for the Baddoch than for the Sheeoch. Relationships between muscle cellularity variables, the density of myonuclei and responses to temperature mere investigated using multivariate statistical techniques. These revealed highly significant temperature effects (P<0.001) at hatch (H) and first feeding (FF) and significant interactions between population and temperature (P<0.001), indicating that Baddoch and Sheeoch salmon responded differently to the two temperature regimes. The total cross-sectional area of white muscle (WF.ta) at the adipose fin was relatively independent of temperature at hatch and first feeding in the Sheeoch population. In contrast, for alevins of Baddoch origin, WF.ta was 18.9% (H) and 30.5% (FF) higher in fish incubated at Baddoch than at Sheeoch temperatures. At hatch, there were 15.6% more white muscle fibres (WF.no) at the cooler incubation temperature in fish of Sheeoch origin and 6.0% more in fish of Baddoch origin. However, by first feeding, the difference in WF.no between temperatures had narrowed to 7.2% in the Sheeoch fish and increased to 17.4% in the Baddoch population In contrast, at hatch, the density of myonuclei was 59.8% higher at the warmer incubation temperature in the Sheeoch population and 23.5% higher in the Baddoch population, but differences were less evident at first feeding. In Baddoch fish, 22.5% of the total muscle nuclei mere actively dividing at first feeding, as assessed by staining for proliferating cell nuclear antigen (PCNA), Of the PCNA-positive nuclei, 78% were present in cells that stained for the c-met tyrosine kinase receptor, a marker of satellite cells and their division products. The proportion of c-met-positive ...